Adobe InDesign CS2 how-tos : 100 essential techniques - Cruise, John (Adobe Press, 2006)
InDesign CS2 is more than just a powerful page layout tool: As part of Adobe's new Creative Suite 2 (which includes Photoshop, Illustrator, GoLive, and Acrobat), it's a key component of an overall design workflow that lets users work seamlessly among all of their graphics applications to create spectacular layouts. This info-packed guide lets you get right down to work by focusing on just the InDesign CS2 features you're most likely to use and showcasing each in a stand-alone tip--complete with a relevant hint or two and a graphic example. In this fashion, you learn as you go, exploring the program in a way that makes sense to you. Before you know it, you'll be using the Bridge to manage your files, object styles to format your images, and snippets to save layout parts for reuse and much, much more!